Supplementation of Red Bean (Phaseolus vulgaris L) Extract Decreased Malondialdehyde (MDA) Levels of Stressly Induced Activity of Male Wistar Rats (Rattus norvegicus) - Septivani, Gina; Pangkahila, Wimpie; Pinatih, Indraguna (Metamorfosa: Journal of Biological Sciences, 2019)
This study aims to prove that supplementation of  red bean extract ( Phaseolus vulgaris L) decreased malondialdehyde (MDA) levels of stressly induced activity of male wistar rats ( Rattus norvegicus ). This research was an experimental with pre-test post-test control group design. The rats were randomly divides into 3 groups: negatif control group (P0), positive control group (treated with overtraining and aquades 2ml/P1), and treatment group (treated with supllementation of red bean extract 650 mg/200 g body weight and overtraining/P2). The rats were swam for 45 minutes everyday. Data were analysed by one way anova test. The study showed that MDA level pretest of the each group was 69,70±0,52 mmol/L; 70,12±0,54 mmol/L and 69,59±0,51 mmol/L respectively. MDA level posttest of the each group was 69,66±0,27 mmol/L; 90,08±0,20 mmol/L and 62,85±0,50 mmol/L respectively. From the result of this study, it can be concluded that suplementation of red bean extract ( Phaseolus vulgaris L) decreased malondialdehyde (MDA) levels of stressly induced activity of male wistar rats ( Rattus norvegicus ). Keyword: red bean (Phaseolus vulgaris L) extract, rats, overtraining, MDA, stress oxidative.